Embodied visual programming for robot control - Konstantopoulos, Stasinos; Lydakis, Andreas; Gkikakis, Antonios-Emmanouil (HRI '14 : proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction : March 3-6, 2014, Bielefeld, Germany, 2014)
In this paper we motivate and present our embodied visual programming research plan, aiming at allowing end-users without any technical expertise to define complex robot behaviours. The core idea is to combine visual programming with the sensing and actuation capabilities of robots and with teleoperated demonstrations of what needs to be achieved.